Satisfaction with care in men with prostate cancer. (27th February 2019) - Forgione, Michelle; Sara, Sally; Vincent, Andrew D.; Borg, Martin; Moretti, Kim; O'Callaghan, Michael E.
Abstract: Purpose: This study aims to describe: (a) the proportion of prostate cancer patients satisfied with treatment, (b) how satisfaction changes after treatment, and (c) predictors of patient satisfaction including demographic, symptom‐related and treatment variables. Method: Self‐reported quality of life and satisfaction questionnaire (UCLA Expanded Prostate Cancer Index Composite [EPIC] 26), and demographics were obtained from the South Australian Prostate Cancer Clinical Outcomes Collaborative (SA‐PCCOC) database. Responses were obtained pre‐treatment (radical prostatectomy or external beam radiation therapy) and 6, 12 and 24 months post‐treatment, for patients diagnosed between 2009 and 2013. Mixed‐effects models were used to estimate mean and change in satisfaction, and to identify predictive factors. Results: SA‐PCCOC is a prospective, prostate cancer specific registry established in 1998, of which 1, 713 patients were eligible for inclusion and 434 available for analysis. Overall, the majority of patients who completed questionnaires were satisfied with their treatment (82%). Satisfaction with care did not change over time post‐treatment in multivariable analysis ( p  = 0.08). Conclusions: Satisfaction with treatment is typically high among prostate cancer patients. Satisfaction did not change with time after treatment and appears to be associated with baseline hormonal scores and changes in hormonal scores post‐treatment.